2018
DOI: 10.1002/adhm.201701415
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3D Hybrid Nanofiber Aerogels Coupled with BMP‐2 Peptides for Cranial Bone Regeneration

Abstract: An ideal synthetic bone graft is a combination of the porous and nanofibrous structure presented by natural bone tissue as well as osteoinductive biochemical factors such as bone morphogenetic protein 2 (BMP-2). In this work, ultralight 3D hybrid nanofiber aerogels composed of electrospun PLGA-collagen-gelatin and Sr-Cu codoped bioactive glass fibers with incorporation of heptaglutamate E7 domain specific BMP-2 peptides have been developed and evaluated for their potential in cranial bone defect healing. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
98
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 52 publications
(68 reference statements)
1
98
0
1
Order By: Relevance
“…More specifically, the sol–gel route allows the simplification of BAG to ternary (SiO 2 ‐CaO‐P 2 O 5 ) and binary (SiO 2 ‐CaO) systems containing up to 90 wt% SiO 2 (instead of 60 wt% for melt‐derived BAG) . Another key advantage of the sol–gel process is the diversity of shapes it offers: BAG can be fabricated under the form of nanoparticles, fibers, coating, particulates, monoliths or scaffolds …”
Section: Glassesmentioning
confidence: 99%
“…More specifically, the sol–gel route allows the simplification of BAG to ternary (SiO 2 ‐CaO‐P 2 O 5 ) and binary (SiO 2 ‐CaO) systems containing up to 90 wt% SiO 2 (instead of 60 wt% for melt‐derived BAG) . Another key advantage of the sol–gel process is the diversity of shapes it offers: BAG can be fabricated under the form of nanoparticles, fibers, coating, particulates, monoliths or scaffolds …”
Section: Glassesmentioning
confidence: 99%
“…When implanted in rat calvarium defects for 6 weeks, FGF2/FGF18 loading substantially increased the hard tissue ingrowth regions, which was evidenced by the highly increased bone volume and bone surface density from micro‐CT images. In the study of Weng et al, ultralight 3D fibrous aerogels composed of electrospun PLGA/collagen/gelatin fibers and Sr–Cu co‐doped bioactive glass fibers were constructed by combining electrospinning and freeze‐drying methods for cranial bone defect healing ( Figure a). Heptaglutamate E7 domain specific BMP‐2 peptides were further conjugated onto the optimized scaffolds for osteoinductive feature.…”
Section: Applications In Biomedical Fieldsmentioning
confidence: 99%
“…c3/c6) Peptide‐loaded aerogels group (4w/8w). Reproduced with permission . Copyright 2018, John Wiley and Sons.…”
Section: Applications In Biomedical Fieldsmentioning
confidence: 99%
“…Similar to grinding in liquid nitrogen, sonication (Lee et al, ; Weng et al, ), smashing (Duan et al, ) and aminolysis (Ahmad et al, ) were also applied to broken small pieces of nanofibers, and the subsequent process was similar to the dispersion‐shaping technique. Since then, a series of similar studies have successfully fabricated nanofibrous aerogels of different materials by the dispersion‐shaping technique and explored their potential for application in bone tissue engineering.…”
Section: Fabrication Of 3d Nanofibrous Scaffoldsmentioning
confidence: 99%
“…In addition, due to the good physical adsorption capacity of hydroxyapatite for peptide drugs, E7‐BMP‐2 peptide (a BMP‐2 derived peptide) could be loaded on the hydroxyapatite‐rich nanofibers after biomineralization, thereby achieving a sustained release and preserving the biological activity of the loaded peptides. In vivo experiments have shown that E7‐BMP‐2 peptide loaded three‐dimensional (3D) nanofibrous scaffolds can better promote the bone regeneration in defect area than unmodified ones (Luo et al, ; Weng et al, ).…”
Section: Biomodification Of 3d Nanofibrous Scaffoldsmentioning
confidence: 99%